Proper Hand Washing for School Children - Amy Simonne (EDIS)
Germs can hide under long fingernails and on dirty hands. Keeping your fingernails short and washing your hands often, are the most important things you can do to stop germs from making you sick. Germs that cause illnesses such as colds, flu, diarrhea, and vomiting can get on your hands from touching things around you. People, pets, raw foods, toys, soil, and objects used in our daily lives can all have germs on them. When you wash your hands properly it helps remove germs from your hands. This document is FCS 8783-Eng, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date November 2005.